2010
DOI: 10.1016/j.neuropsychologia.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy in two attention networks is associated with performance on a Flanker task in neurodegenerative disease

Abstract: This study investigated the neurobiological basis of attentional control dysfunction in neurodegenerative disease by determining the effect of regional brain atrophy on Flanker task performance of neurodegenerative patients. We hypothesized that atrophy in DLPFC and ACC would be significantly associated with decreased attentional control performance on the Flanker task. We used voxel-based morphometry (VBM) to measure the relationship between MRI measures of regional grey matter atrophy and performance on a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 59 publications
4
44
0
Order By: Relevance
“…23,32 Parietal-frontal networks underlie attentional control and are important for good performance on the Flanker paradigm. 25 Although we expected both groups to be impaired on the Set-Shifting Test, neither was impaired after the MMSE adjustment. This lack of group differences may be attributable to the diffuse neuroanatomical substrates of set-shifting and to the performance variability in the patients.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…23,32 Parietal-frontal networks underlie attentional control and are important for good performance on the Flanker paradigm. 25 Although we expected both groups to be impaired on the Set-Shifting Test, neither was impaired after the MMSE adjustment. This lack of group differences may be attributable to the diffuse neuroanatomical substrates of set-shifting and to the performance variability in the patients.…”
Section: Resultsmentioning
confidence: 93%
“…17 Integrity of the lateral prefrontal cortex is important for the cognitive aspects of executive functions, including verbal fluency, 19 antisaccade accuracy, 20,21 working memory, 22,23 and controlled attention. 24,25 Although integrity of both the lateral and ventromedial prefrontal cortex is important for social decision-making and behavior, the ventromedial aspects are most critical. [26][27][28] Patients with bvFTD usually exhibit impairments in social behavior before cognitive aspects of executive functions, which probably reflects the spread of the disease from the ventromedial to dorsolateral prefrontal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…A volumetric MRI study showed that there was an association between left hemisphere dorsolateral prefrontal cortex and anterior cingulate cortex atrophy and poorer attentional control accuracy. In the right hemisphere, atrophy of the temporal-parietal junction and ventrolateral and dorsolateral prefrontal cortices were associated with slower response times during attentional control on accurate trials [53]. This evidence from neuroimaging studies suggests that an executive deficit was caused by brain disorders in widespread regions that included prefrontal cortex, parietal lobe, and cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Nor is it clear whether WM is the primary mediator of RT. Associations have emerged with GM volume within the cerebellum (Menzies et al 2007); fusiform gyrus (Perneczky et al 2011); temporo-parietal junction (Luks et al 2010); cingulate and parietal cortices along with putamen/caudate and amygdala (Menzies et al 2007); and several regions within the frontal lobes (Menzies et al 2007;Luks et al 2010;Perneczky et al 2011).…”
Section: Rt and The Brainmentioning
confidence: 99%